Assessment of Male and Female Nursing Students' Perception of Male Nurses Role at Makkah, KSA - Maram Taher Alghabashi, Hala Yehia Sayed, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: More men in nursing are critical to meet predicted global shortages in the nursing workforce, and to promote gender equality in the profession. Male nurses face challenges in their education and practice because of their gender and stereotypes associated with being a male in a female dominated profession. Despite the constant changes that impact healthcare, the sex imbalance of the nursing education remains constant. Aim: Assess students’ perceptions about male nursing and compare students’ perceptions about male nursing. Material and Method: Method: A cross-sectional descriptive design was used in this study. To assess the students’ perceptions about male nursing which was contained three sections. The first part of the questionnaire included socio demographic data, second part of the questionnaire included questions about perceptions of both female and male students about position of males in nursing career while questions regarding effects of recruiting males to nursing career were included in the third part. The total sample of the study was 120 male & female nursing students were selected from each class level. Results: There were highly statistically significant differences of career preferences among students regarding clinics are seen suitable for men to work after graduation in emergency (0.005). In addition, there was statistically significant differences of male & female students' in relation to working place preferences of male students after graduation as administrator (0.03). Conclusion: Male & female students expectations regarding; working place preferences of students after graduation in emergency primary care, hospital ward, instructor in college, male & female students prefer emergency, operating room, intensive care unit, medical & surgical ward as clinics suitable for men after graduation and male and female perceived that males will change anything in image of nursing, will improve image of nursing, will change anything in the status of nursing and will improve the status of nursing. As well as they refuse the nursing profession to be a female profession. Recommendations: Faculties of nursing should encourage and organize the admission of men to nursing profession to be fruitful through policies, rules, regulations, determining male role identity, job description, rights…. etc. Admission of men in nursing profession to decrease the severe shortage considering the suitable areas for men to work in. Design and implement orientation training programs about nursing career and profession for men students before admission.